2020
DOI: 10.1108/vjikms-10-2018-0092
|View full text |Cite
|
Sign up to set email alerts
|

The technology tasks fit, its impact on the use of information system, performance and users’ satisfaction

Abstract: Purpose Find out how the employees’ performance on the implementation of the hotel reservation information system. Therefore, this paper aims to examine the effect of the task-technology fit (TTF) on the use of information systems, as well as its effect on user performance and satisfaction. Design/methodology/approach This research type is explanatory research. In explanatory research, the aim is to provide an explanation related to the causal relationship between variables and hypothesis testing. The unit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
(80 reference statements)
2
6
0
1
Order By: Relevance
“…Since the study uses 20 indicators, the minimum sample size is 100. So, the total number of 130 respondents is considered to represent the number of samples used [17]. The measurement scale used in this study uses a Likert scale with a scale of 1-4 with a scale value including strongly disagree (1), disagree (2), Agree (3) and Strongly Agree (4).…”
Section: Methodsmentioning
confidence: 99%
“…Since the study uses 20 indicators, the minimum sample size is 100. So, the total number of 130 respondents is considered to represent the number of samples used [17]. The measurement scale used in this study uses a Likert scale with a scale of 1-4 with a scale value including strongly disagree (1), disagree (2), Agree (3) and Strongly Agree (4).…”
Section: Methodsmentioning
confidence: 99%
“…Kee and Rubel (2021) reported that new technological innovation could disadvantage an organization when the established power structure prevents it from fully exploiting the innovation; thus, technological adaptation provides value. Ratna et al (2020) advocate that IT adaptation leads to increased end-user performance as users invest time and effort to adapt a given IT; they are more motivated to utilize it to realize the expected benefits from their invested efforts. Bhattacherjee and Harris (2009) also consider IT adaptation a predictor of IT performance and find a significant relationship.…”
Section: Technology Adaptation and Technology Innovation Performancementioning
confidence: 99%
“…Through the application of information systems and technology companies need to prepare human resources (HR). Ease in various aspects of business activities cannot be separated from the role of IT which is able to provide innovation in every development (Ratna et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%